Short-Course Induction Treatment with Intrathecal Amphotericin B Lipid Emulsion for HIV Infected Patients with Cryptococcal Meningitis - Gerardo Alvarez-Uria; Manoranjan Midde; Raghavakalyan Pakam; Pradeep Sukumar Yalla; Praveen Kumar Naik; Raghuprakash Reddy (Journal of Tropical Medicine)
Cryptococcal meningitis (CM) is a common cause of death among HIV infected patients in developing countries, especially in sub-Saharan Africa. In this observational HIV cohort study in a resource-limited setting in India, we compared the standard two-week intravenous amphotericin B deoxycholate (AmBd) (Regimen I) with one week of intravenous AmBd along with daily therapeutic lumbar punctures and intrathecal AmB lipid emulsion (Regimen II) during the intensive phase of CM treatment. 78 patients received Regimen I and 45 patients received Regimen II. After adjustment for baseline characteristics (gender, age, altered mental status or seizures at presentation, CD4 cell count, white blood cells, cerebrospinal fluid white cells, and haemoglobin), the use of Regimen II was associated with a significant relative risk reduction in mortality (adjusted hazard ratio 0.4, 95% confidence interval, 0.22–0.76) and 26.7% absolute risk reduction (95% confidence interval, 9.9–43.5) at 12 weeks. The use of Regimen II resulted in lower costs of drugs and hospital admission days. Since the study is observational in nature, we should be cautious about our results. However, the good tolerability of intrathecal administration of AmB lipid emulsion and the clinically important mortality reduction observed with the short-course induction treatment warrant further research, ideally through a randomized clinical trial.